Serum osteopontin is a biomarker of severe fibrosis and portal hypertension in human and murine schistosomiasis mansoni. Issue 13 (December 2016) - Pereira, Thiago Almeida; Syn, Wing-Kin; Pereira, Fausto E.L.; Lambertucci, José Roberto; Secor, William Evan; Diehl, Anna Mae
Graphical abstract: Highlights: Osteopontin distinguishes severe from mild schistosomiasis in mice and humans. Osteopontin is a novel morbidity biomarker in human and murine schistosomiasis. Failure to modulate osteopontin expression may contribute to severe fibrosis. Abstract: Schistosomiasis is a major cause of fibrosis and portal hypertension. The reason 4–10% of infected subjects develops hepatosplenic schistosomiasis remains unclear. Chronically infected male CBA/J mice reproduce the dichotomic forms of human schistosomiasis. Most mice (80%) develop moderate splenomegaly syndrome (similar to hepatointestinal disease in humans) and 20% present severe hypersplenomegaly syndrome (analogous to human hepatosplenic disease). We demonstrated that the profibrogenic molecule osteopontin discriminates between mice with severe and mild disease and could be a novel morbidity biomarker in murine and human schistosomiasis. Failure to downregulate osteopontin during the chronic phase may explain why hepatosplenic subjects develop severe fibrosis.